Reconstructing Pitu Ulunna Salu Cultural Identity as a Model for Socio-Religious Conflict Reconciliation in Mamasa - Mahyuddin; Mohd Azmir Mohd Nizah; Abd Hakim Mohad Ramli; Rasyid, Abd; Deasy, Deasy; Rahmi, Nur (Palita: Journal of Social Religion Research, 2025)
This study analyzed the collective identity construction of Pitu Ulunna Salu (PUS) in strengthening peacebuilding efforts in Mamasa, West Sulawesi. The reconstruction of PUS became a peace mission doctrine that reshaped public perceptions of brotherhood and harmony after the regional expansion conflicts, which had triggered ethnic and religious disintegration. The research employed a qualitative case study design, collecting data through in-depth interviews and secondary sources. The findings showed that the reconstruction of PUS cultural identity, as part of the historical alliance of traditional institutions served as a catalyst for reconciliation and conflict mitigation in Mamasa. The community’s adherence to traditional values and communal leadership was instrumental in maintaining social harmony, while youth were playing a pivotal role in the ongoing transformation of conflict. This study introduced a conceptual model of Cultural Identity-Based Peacebuilding, which integrated three key elements: traditional authority, collective memory, and youth participation. The model explained how indigenous identity reconstruction functioned not only as cultural preservation but also as a strategic sociopolitical mechanism for sustainable peace. The novelty of this research lay in framing local identity as an active agent in transforming post conflict societies rather than as a passive cultural symbol. A deeper understanding of PUS identity formation enabled the effective application of regional identity in peace processes, enhancing the sustainability of reconciliation. This study provided an empirical and theoretical contribution by bridging indigenous knowledge and contemporary peace studies, offering a replicable model for other multicultural post-conflict contexts.  Keywords: Conflict Reconciliation, Pitu Ulunna Salu, Social Construction, Peacebuilding